Analysis of dimensions of sella turcica in patients with mandibular prognathism - Čutović Tatjana; Pavlović Jasna; Kozomara Ružica (Vojnosanitetski Pregled, 2008)
Introduction/Aim. Patients with mandibular prognathism as dominant symptom have disordered sagittal interjaw relations that make prominent appearance to this dental craniofacial anomaly beside hyperplastic mandibles and inverted front teeth overlap. The aim of this study was to examine the differences in dimensions of sella turcica in patients with mandibular prognathism and in eugnathic. Methods. On profile teleradiographs of 30 eugnathic control and 30 patients with mandibular prognathism, three parameters, which represent dimensions of sella turcica, were measured (surface, width and depth). Results. Statistically significant difference in values between the groups was found. All the three measured parameters were significantly higher in the patients with mandibular prognathism (p < 0.01). Conclusion. In the patients with mandibular prognathism all the measured dimensions of sella turcica were bigger, and so was sella turcica, but that enlargement was not in correlation with the degree of anomaly itself.